Romantic love evolved by co-opting mother-infant bonding - Bode, Adam (Frontiers in Psychology, 2023)
For almost 25 years, the predominant evolutionary theory of romantic love has been Fisher's theory of independent emotion systems. That theory suggests that sex drive, romantic attraction (romantic love), and attachment are associated with distinct neurobiological and endocrinological systems which evolved independently of each other. Psychological and neurobiological evidence, however, suggest that a competing theory requires attention. A theory of co-opting mother-infant bonding sometime in the recent evolutionary history of humans may partially account for the evolution of romantic love. I present a case for this theory and a new approach to the science of romantic love drawing on human psychological, neurobiological, and (neuro)endocrinological studies as well as animal studies. The hope is that this theoretical review, along with other publications, will generate debate in the literature about the merits of the theory of co-opting mother-infant bonding and a new evolutionary approach to the science of romantic love.